The Effects of Environment, Facilities and Organizational Culture Towards the Successfulness of Tourism Industry in Manis Kidul Village, Kuningan District, West Java - Setiawan, Agung; Sungkawa, Khaeril; Sinaga, Obsatar (International Journal of Psychosocial Rehabilitation, 2020)
This research is to determine the perception of the Manis Kidul village community towards the development of the Manis Kidul village as a tourism destination in Kuningan District, knowing the concern of the Manis Kidul village community in preserving the environment and local wisdom as a form of tourism product that can be used in tourism development. The perception of the people and the attitude towards the progress of the Manis Kidul would affect the tourism industry in the area. Thus, the positive perception would determine the success of the tourism industry whereas negative perception from the citizen would result the delay in the progress of the tourism development in Manis Kidul Village. This research investigates the impact of the environment, facilities and the organizational culture towards the successfulness of tourism industry in the district of Kuningan and found that these three factors contribute to the successfulness of tourism industry in the area. In this research, the initiative from the government and the agencies is vital in order to enhance the image and reputation of Manis Kidul Village.